Big apple gangsters: the rise and decline of the mob in New York - Sussman, Jeffrey (Rowman & Littlefield, 2020)
"Through profiles of the most colorful and powerful crime bosses, gang members, corrupt cops, and numerous mob associates as well as pivotal events in the history of organized crime, Big Apple Gangsters reveals just how influential the mob has been in controlling large numbers of business not just in New York, but also in other cities"--